PENGARUH LINGKUNGAN KELUARGA SIKAP BELAJAR EKONOMI DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI SISWA SMAN DI KOTA BUKITTINGGI - Ice Suci Rahayu; Yunia Wardi (Jurnal Kajian Pendidikan Ekonomi, 2016)
The objectives to be achieved in this study, namely to analyze:the familyenvironment, Economic influence learning,and motivationinfluence toward learning outcomes of students in economic subjects SMAN In Bukittinggi. The type of this research is a associative deskriptive. The technique ofsamplingin this studyistheProportional  Stratified sampling, with a sample of 339 students.Data collected throughinterviews, questionnaires, anddocumentationas a referencein research.Metodeanalysis isthe Path analysis. classifiedintoquantitative study usingsurvey research methods. Totesthe hypothesisby usingt test.The results showedthat: 1) the familyenvironmentsignificantly influence themotivation to learn. 2) learning attitudeeconomysignificantly influence themotivation to learn. 3) the familyenvironment significant effect onlearning outcomes. 4) the attitude ofstudying economicssignificant effect onlearning outcomes. 5) motivation to learna significant effect onlearning outcomes.  Keywords: Family Environment, EconomyLearningAttitude, Motivation, Learning Outcomes